ASSISTANCE TO THE PT PELINDO MARINE SERVICE EMPLOYEE COOPERATIVE IN THE PROCESS OF FORMING A SUBSIDIARY - Khakim, M Azizul (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The background for this dedication is the PT Pelindo Marine Service Employee Cooperative which will expand its business, marked by the formation of PT Marine Indonesia. The strong commitment of the PT Pelindo Marine Sevice Employee Cooperative to provide excellent service to customers and strengthen support for the Pelindo Group as the holding company, as well as expanding business development are the factors behind this. PT Marine Indonesia is a company engaged in the management of ship licenses and ship repair services. The cooperative asked the authors and colleagues to provide their studies and assessments regarding the formation of this new company. Based on the observations and analysis of the author and the team, a conclusion was drawn that the formation of PT Marine Indonesia was feasible and should have been carried out by the Employee Cooperative of PT Pelindo Marine Service.